Direct time-resolved observation of tungsten nanostructured growth due to helium plasma exposure. (March 2015) - Fiflis, P.; Curreli, D.; Ruzic, D.N.
Abstract Determination of the mechanisms underlying the growth of tungsten fuzz is an important step towards mitigation of fuzz formation. Nanostructured tungsten was produced on resistively heated tungsten wires in a helicon plasma source (maximum flux of 2.5 × 1021 m−2 s−1). Asymmetry in the setup allows for investigation of temperature and flux effects in a single sample. An effort at elucidating the mechanism of formation was made by inspecting SEM micrographs of the nanostructured tungsten at successive fluence steps of helium ions up to a fluence of 1 × 1027 m−2. To create these micrographs a single tungsten sample was exposed to the plasma, removed and inspected with an SEM, and replaced into the plasma. The tungsten surface was marked in several locations so that each micrograph is centred within 200 nm of each previous micrograph. Pitting of the surface (diameter 9.5 ± 2.3 nm, fluence (5 ± 2) × 1025 m−2) followed by surface roughening (fluence (9 ± 2) × 1025 m−2) and tendril formation (diameter 30 ± 10 nm, fluence (2 ± 1) × 1026 m−2) is observed, providing evidence of bubble bursting as the mechanism for seeding the growth of the tungsten fuzz.